A two-dimensional conjugated polymer framework with fully sp2-bonded carbon skeleton - Zhuang, Xiaodong; Zhao, Wuxue; Zhang, Fan; Cao, Yu; Liu, Feng; Bia, Shuai; Feng, Xinliang (Polymer Chemistry, 2016)
The synthesis of crystalline two-dimensional (2D) covalent organic frameworks (COFs) with fully unsaturated carbon-carbon backbones via a solution approach remains a great challenge. In this work, we report the first example of an olefin-linked 2D conjugated COF using a Knoevenagel polycondensation reaction of 1,4-phenylene diacetonitrile and three armed aromatic aldehyde. The resulting 2D poly(phenelyenevinylene) framework (2DPPV) possesses a sheet morphology, and a crystalline layered structure featuring a fully sp2-bonded carbon skeleton with pendant cyanide groups. Its unique alternating structure with a serrated configuration has been essentially evaluated using HR-TEM TEM analysis, nitrogen physisorption measurements, PXRD studies and theoretical simulations. Upon thermal and activation treatments, the as-prepared 2DPPV can be facilely converted into porous carbon nanosheets with large specific surface areas of up to 880 m2 g-1 which exhibit an excellent electrochemical performance as supercapacitor electrodes and electrocatalysts for the oxygen reduction reaction. This represents an economic non-template approach to 2D porous carbon materials for energy-related applications.
CRIS-Team Scopus Importer:2023-03-20